Accuracy of Contrast-Enhanced Ultrasound in the Diagnosis of Bile Duct Obstruction - Fontán, F. J. P.; Reboredo, Á. R.; Siso, A. R. (Ultrasound International Open, 2015)
To investigate the ability of contrast-enhanced ultrasound (CEUS) to differentiate benign from malignant lesions causing biliary duct obstruction.Between November 2006 and December 2013, 59 patients with bile duct obstruction of undetermined cause in baseline ultrasound underwent CEUS study. The enhancement and posterior washout were analyzed in real time all along the study duration (5′). The final diagnosis suggested by CEUS was compared with histologic diagnosis (47.5%) or with radiologic follow-up with TC, RM or ERCP.Final diagnoses included 42 malignant lesions (cholangiocarcinoma n=22, metastases n=6, pancreatic carcinoma n=6, hepatocarcinoma n=4, gallbladder carcinoma n=2, ampullary carcinoma n=1 and lymphoma n=1) and 17 benign lesions (lithiasis or biliary sludge n=15, xanthogranulomatous cholecystitis n=1 and indeterminate n=1). CEUS accuracy compared with final diagnoses based on combined reference standard was 86.4%. CEUS correctly identified 36 of 42 malignant lesions (sensibility 85.7%) and 15 of 17 benign lesions (specificity 88.2%). The positive predictive value of CEUS for malignancy was 94.7%, while the negative predictive value was 71.4%.CEUS is useful to differentiate between benign and malignant causes of obstructive jaundice. This technique improves the detection of bile duct invasion in hepatic neoplasms and permits better evaluation of intra- and extraductal extension of hilar hepatobiliary tumors.
Keywords: abdomen; biliary system; ultrasound